PENGARUH HARGA, KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN LOFFLE POP UP DESSERT) - Dimas Erlangga Putra; Dinalestari Purbawati (Jurnal Ilmu Administrasi Bisnis, 2019)
This study aims to determine the effect of price, product quality and word of mouth on purchasing decisions on consumers Loffle Pop Up Dessert. The type of research used to examine is explanatory. The sample of this study was 100 respondents with its spread using the non-probability sampling method (accidental sampling) which directly met with consumers at the outlet. Data were analyzed using SPSS 25 for windows with validity tests, reliability tests, cross table analysis, correlation coefficient tests, coefficient of determination, simple and multiple regression analysis, and significance tests (t test and F test). The results of this study indicate that there is a positive effects of the price, product quality and word of mouth variables on the purchase decision variable. The price variable has an effect of 0.542 while the product quality variable has an effect of 0.561 and also the word of mouth variable has an effect of 0.362. Simultaneously together the price, product quality and word of mouth variables contributed 58.0% to the purchase decision of Loffle Pop Up Dessert. The results show that the product quality variable has a greater influence than the price variable which is supported by a coefficient of determination of 30.3%. Based on the results of this study it is recommended that Loffle Pop Up Dessert be more aggressive in promoting to be able to provide bait to potential customers for the creation of positive WOM.